Hostel occupant's satisfaction towards facility performance in private funding initiative (PFI) institutional accommodation / Hairul Reazuan Asmayadi - Asmayadi, Hairul Reazuan (2015)
This study believes that one of the most ignored areas in studies pertaining to issues involving university students is their satisfaction contact with hostel physical environment. Even, in Private Funding Initiative (PFI) concept, developers pay little concern on hostel built environment as compared to commercial properties. Therefore, the hostel occupants' satisfaction and their sensations interaction with indoor environment were not fully discovered. Thus, this study was designed to explore these areas with three primary objectives; identifying the dimension of facilities performance, examining the significant influence of facilities performance, and identifying the least and most significance dimension to hostel occupants' satisfaction. Data were obtained from questionnaire distributed randomly to a sample of 315 respondents from PFI's hostel blocks in UiTM Puncak Alam campus, Selangor. The data comprised four sections measure the Indoor Environment (IE), Surrounding Facilities (SF), satisfaction and demographic profiles. These were analysed using frequencies, exploratory factor analysis (EFA), and multiple regression analysis. Principal component analysis with VARIMAX rotation in EFA indicated variation in proposed-structural component where IE formed and extracted into six sub-dimensions, and SF factored 10 subdimensions. Later, the sub-dimensions were renamed in accordance to its characteristic that underlying the factor. Three items in IE and four items in SF were collapsed in structural dimensionality. EFA data were then performing the multiple regression analysis and resulted to medium-high correlation for both dimensions. ANOVA regression test indicated both models were fits for the analysis. The total variance explained 42% in IE and 60% in SF. Of six items in IE, only five items were identified significant to be included in the model, meanwhile, health and safety are the greatest influence and most importance on hostel occupants' satisfaction. Six items out of 10 were seen significant in SF and internet connection placed the greatest influence on hostel occupants' satisfaction. This study requires extension research that in other settings to generalize the result.